THE PENERAPAN ALUR PENANGANAN PASIEN CORONAVIRUS DISEASE 2019 (COVID-19) OLEH PETUGAS KESEHATAN DAN GUGUS TUGAS PENANGGULANGAN COVID-19 DI KABUPATEN BULUKUMBA - Wahida; Muhammad basri (Jurnal Administrasi Negara, 2020)
Corona Virus Diasease-2019 or COVID-19 is infectious disease that spreads. Government has responded and issued pathways as guidance. During the implementation of the pathways, several obstacles have been encountered by healthcare workers and government taskforce in Bulukumba. This study aimed at evaluating the implementation of the COVID-19 patients treatment performed by the workers and the taskforce. This study used qualitative approach with cse study design. The data of this study was obtained through structured interview and document review. There were 12 informants, consisting of healthcareworkers from Bulukumba public hospital and Health Department of Bulukumba. The data was analyzed through Miles & Huberman approach and thematic analysis. The study showed that the pathway of COVID-19 patient treatment has not been implemented optimally due to lack of dissemination. Inconsistent between central and local governments and negative stigma by communities became obstacles in its implementation. Lesson learnt from the implementation included coordination across sectors and facilities/equipment are crucially needed. This study recommended the obedience to pathways by healthcareworkers and any taskforces, government concistency, coordination and cooperation in handling similar communicable diseases in the future.